Implications of circular economy practices for firms in the integrated waste sector - Agyapong, Daniel; Agyapong, Gloria K. Q.; Ofori, Daniel; Light, Osman; Frimpong, Stephanie Efua (Frontiers in Sustainability, 2025)
IntroductionThis study examined the effects of circular economy practices on the integrated waste management industry, drawing on the stakeholder theory. This study examined how the performance of Ghanaian waste management companies is affected by circular economy strategies, particularly upcycling and was recovery.MethodsAbout 7,190 firms registered with the Environmental Service Providers Association (ESPA) formed the population of the study, out of which the sample yielded 524 valid responses, which was analysed using PLS-SEM and Partial Correlation Analysis. PLS was adopted because it integrates factor and route analyses into significantly more rigorous statistical processes. In addition, the Partial Correlation network structure was adopted to explain how the nodes or variables are related to one another.ResultsThe results demonstrate that upcycling has a favorable and considerable impact on the economic performance (β = 0.475, t = 4.495, p = 0.000), social performance (β = 0.403, t = 3.132, p = 0.002), and corporate governance performance (β = 0.455, t = 3.670, p = 0.000) of the firms. Furthermore, waste recovery improved the performance of waste management companies in terms of performance, specifically economic performance (β = 0.333, t = 3.183, p = 0.001), environmental performance (β = 0.583, t = 4.641, p = 0.000), social performance (β = 0.402, t = 3.157, p = 0.000), and corporate governance performance (β = 0.250, t = 2. 024, p = 0.048) indices.DiscussionFinally, circular economy practices have a substantial impact on firms’ financial stability and investment readiness. It was concluded that waste management companies that excel in undertaking circular economy activities such as remanufacturing, trash recycling, and refurbishing are more likely to draw clients who want green activities in addition to their current needs. Additionally, these actions increase efficiency, which lowers operational expenses and improves governance-related concerns, including management training on these procedures and implementation of policies in compliance with the law.